Influence of personality factors and loneliness on mental health among undergraduates of distance learning, University of Ibadan (2015)
Over many decades, issue of mental health has not received the kind of attention that it deserves and has been neglected in many parts of the world. This neglect is a result of the lack of knowledge and the misunderstanding of mental health and the fear that the findings may reveal a mentally ill person. More sadly in Nigeria, the stigma associated with mental health is frequently encountered, often being regarded as a taboo and is seldom discussed. This study in\ tigated the influence ofpersonality factors and loneliness on mental health among undergraduates o distance learning of University of Ibadan. This study adc_ ted a cross-sectional survey design using questionnaire on the variables of the study. Data was collected from a sample size of three hundred and twenty-nine (329) distance learning undergraduates in the University of Ibadan using randomization technique. In the process, four hypotheses were generated and tested using appropriate inferential statistical tools. The results of regressions showed that extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience jointly predicted mental health at {.R2=.149; F(5, 323)=18.291;P< .05} & only extraversion and conscientiousness had significant independent influence on mental health at; {P< .05}. It was also found that loneliness had significant influence on mental health among UI.DLCstudents; (t (327)=2.499; p< .05}. Further, the result indicates that age had no significant influence on mental health among UI.DLC students; (t (327) =-l. 774; p> .05}.It was found that gender had no significant influence on mental health among UI.DLC students; (t (327); =1.736; p> .05}.This study concluded that Big-Five Personality factors and loneliness predicted mental health & that only extraversion and conscientiousness had significant independent influence on mental health among the population studied. Also age and gender did not influence mental health. One of the limitations of the study is the use of structured questionnaire which predisposed the data to random response error. However, it is suggested that further study should combine interview method with questionnaire to obtain more empirical findings